Intraoperative Hemodynamic Disorders in Adolescent with Lordoscoliosis During Correction of Spinal Deformity: Clinical Case and Brief Literature Review - Anastasiya A. Ivanova; Sergey G. Volkov; Dmitry S. Lukyanov; Maya N. Lebedeva (Вопросы современной педиатрии)
Background. The intraoperative prone position of patients is risk factor of hemodynamic instability development especially in patients with lordoscoliosis due to smaller chest volume. Clinical case description. 15-year-old female patient was admitted for planned surgical correction of grade IV lordoscoliosis. Arterial hypotension has developed during surgery, that could not be corrected by increased infusion therapy rate, vasopressors, and changing anesthetic. Operation has been stopped. No significant anatomical and functional changes in cardiovascular system were revealed during the postoperative period. The patient was taken back to the operating room five days later. However, patient’s positioning has been changed: the Jackson table module with chest and pelvic bone support pads was replaced with standard one with surgical linen placed under the chest and iliac crests. Propofol was the anesthetic of choice. The course of anesthesia was within normal. Conclusion. Preoperative examination of patients with lordoscoliosis should include CT examination of the spine and chest to evaluate the spinal penetration index. Intraoperative positioning should be performed in a way to reduce negative effect of inevitable chest compression. It is preferable to use total intravenous anesthesia. All the above is crucial to minimize the risk of intraoperative hemodynamic instability.